Propuesta de ingeniería conceptual: proceso de extracción del aceite esencial de las cáscaras de naranja obtenidas en panaderías del sector Ricaurte de Bogotá utilizando el método Soxhlet con enfoque en la química verde (2023)
The objective of this research work was to develop a conceptual engineering proposal for the extraction process of essential oil (EO) from orange peels obtained in bakeries in the Ricaurte sector of Bogotá using the Soxhlet method with a focus on green chemistry. The EO was obtained experimentally by bringing into contact and at a certain temperature range, a 1:10 ratio of previously treated orange flavedo and isopropyl alcohol, so that a separation was subsequently carried out in order to purify it. An ANOVA system was proposed to determine if performance was affected by particle size (4 mm and 1 cm) and drying temperature (70 °C and 100 °C). Once obtained, the sample with the best performance was characterized physicochemically and sensorially in order to determine some of its characteristics and compare them with the commercial EO to evaluate if there was a significant contrast in the quality of the product. The statistical analysis and quality tests were developed, it was determined that the performance is affected and that the product does not meet the established parameters, since it presents traces of the solvent, affecting several of its particularities, including its purity.